Utilidad del cefadroxilo en leishmaniosis tegumentaria americana con infecciones piógenas sobreagregadas - Navarro Pedro; Silva, Sylvia; De la Parte María A; Colmenares Luis Alfonso; Coraspe Virginia; Garrido Elinor; Redondo, María C (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Abstract: Cutaneous leishmaniosis of the New World (CLNW) is a health problem in rural areas of Venezuela. Patients with muco-cutaneous ulcers tend to present intercurrent infections of the lesions by pyogenic bacteria. After removing skin specimens from the ulcer borders for microscopic demonstration of Leishmania spp amastigotes, forty-one patients with the disease, being treated with cefadroxil per os were studied. Most of the patients came from rural Miranda state, were male adults and had one ulcer on a lower limb. Confirmatory diagnosis was made using the Montenegro test, or Leishmanin immunoserology (IFAT) and demonstration of the presence of parasites in the skin samples. All the patients were positive for the Leishmanin test, while parasites were observed in 51% of the skin smears colored by the Giemsa procedure. After a week of treatment with cefadroxil, bacterial infections were reduced and a decrease in bacterial load was also noted when visualizing the parasite from the skin smears. Patients were treated with intramuscular antimony meglumine for 10-day periods with an intervening rest period. All patients responded adequately to the meglumine antileishmania treatment; the lesions healed and accompanying tributary lymph nodes disappeared. Conclusion: Cefadroxil is a suitable antibiotic for treating intercurrent pyogenic infections in cases of tegumentary leishmaniosis. Since leishmaniosis is considered an emerging disease, a search for appropriate, alternative therapies is required. Resumen: La leishmaniosis tegumentaria americana es un problema de salud en el medio rural venezolano. Las úlceras leishmánicas tienden a infectarse secundariamente por bacterias piógenas. Se evaluaron 41 pacientes con la enfermedad que recibieron cefadroxilo oral previo a la toma de segmentos de piel del borde de las úlceras para la demostración microscópica de Leishmania spp. La mayoría de los pacientes eran adultos masculinos y provenían del medio rural del estado Miranda, con una úlcera única localizada en los miembros inferiores. El diagnóstico inmunoserológico se efectuó por leishmanina y anticuerpos fluorescentes y el de certeza por visualización de amastigotes en frotis coloreados. Los resultados inmunoserológicos fueron positivos en todos los pacientes, mientras que el parásito se observó en 51% de los frotis coloreados con Giemsa. Una semana postratamiento antimicrobiano, los pacientes presentaban mejoría de las infecciones sobreagregadas y también progreso en la visualización del parásito por disminución de la carga bacteriana. Los pacientes fueron tratados con antimoniato de meglumina intramuscular en series de 10 días, con reposo intermedio. Respondieron adecuadamente, las lesiones cicatrizaron y los nódulos satelitales acompañantes desaparecieron. Se concluye que el cefadroxilo es útil para tratar las infecciones piógenas secundarias asociadas en LTA y aumentar la sensibilidad para observar los parásitos en piel. La leishmaniosis considerada como enfermedad emergente, motiva la búsqueda de alternativas terapéuticas adecuadas.